2013
DOI: 10.1016/j.ijpharm.2013.04.080
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial properties of cyclodextrin–antiseptics-complexes determined by microplate laser nephelometry and ATP bioluminescence assay

Abstract: Cyclodextrins (CDs) are able to form inclusion complexes with other molecules, thereby, protecting these guest molecules from degradation, enhancing their biocompatibility or influencing their physiological distribution while retaining their activity. Here, antibacterial effects of CD-complexes with the antiseptics chlorhexidine diacetate (CHX), iodine (IOD) and polihexanide (PHMB) were determined using two different in vitro methods, microplate laser nephelometry and an ATP bioluminescence assay. Laser nephel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Koburger et al (2010) compared the antiseptic efficacies of triclosan, octenidine, PHMB, PVP–iodine, and chlorhexidine digluconate and concluded that when a prolonged contact time is necessary or feasible (such as treatment of mucosal infections) PHMB presents the highest efficacy among the drugs studied. Considering that, there is an increasing interest in the development of novel drug delivery systems to vehicle PHMB as alternatives to improve the clinical effect of this drug to control microbial infections …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Koburger et al (2010) compared the antiseptic efficacies of triclosan, octenidine, PHMB, PVP–iodine, and chlorhexidine digluconate and concluded that when a prolonged contact time is necessary or feasible (such as treatment of mucosal infections) PHMB presents the highest efficacy among the drugs studied. Considering that, there is an increasing interest in the development of novel drug delivery systems to vehicle PHMB as alternatives to improve the clinical effect of this drug to control microbial infections …”
Section: Introductionmentioning
confidence: 99%
“…Considering that, there is an increasing interest in the development of novel drug delivery systems to vehicle PHMB as alternatives to improve the clinical effect of this drug to control microbial infections. 11,12 The efficacy of antimicrobial agents in the treatment of oral infections is not solely related to in vitro antimicrobial activity. To be adequately effective, it is necessary to achieve a proper drug supply for an extended period.…”
Section: Introductionmentioning
confidence: 99%
“…Strain maintenance was performed on Columbia agar plates with 5% sheep blood (Biomeriéux, France). Bacterial suspensions were prepared in CASO medium (Oxoid, UK) according to Finger et al [16]. …”
Section: Cultivation Of Bacteriamentioning
confidence: 99%
“…Good agreement was obtained between the bioluminescence method and laser nephelometry when antibacterial prop erties of a series of cyclodextrin complexes were evaluat ed [36]. To assess the efficiency of new chemical disinfec tants, standard techniques developed by the European Committee for Standardization, EN 1276 and EN 13727 in particular, are used.…”
Section: Determination Of Intracellular Atp Content In Individual Culmentioning
confidence: 99%